The Role of the Mosque Prosperity Agency Gathering Forum in Conflict Management of Mosque Administrators in Medan City / Peran Forum Silaturahmi Badan Kemakmuran Masjid dalam Manajemen Konflik Pengurus Masjid di Kota Medan - Silvia Vinka Syahfitri; Waizul Qarni (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2026)
Conflict among mosque administrators is an important issue in the governance of religious organizations, particularly when it is triggered by financial management, leadership, and differing interests among administrators. Previous studies have discussed mosque conflict and management, but empirical studies that specifically examine the role of the Mosque Prosperity Agency Friendship Forum in conflict management remain limited. This study aims to analyze the role of the Mosque Prosperity Agency Friendship Forum in managing conflicts among mosque administrators in Medan City. This research employed a descriptive qualitative approach, with the main research site at Nurul Islam Mosque, Jalan Karya Number 203, Karang Berombak, Medan Barat District, Medan City. Data were collected through observation, in-depth interviews with two key informants, namely the Chairperson and Treasurer of the North Sumatra Regional Board of the Mosque Prosperity Agency Friendship Forum, and literature study. The data were analyzed through data reduction, data display, and conclusion drawing. The findings show that conflicts among mosque administrators include structural, administrative, and interest-based conflicts. The forum plays a role as mediator, facilitator, and assistant through strengthening financial systems, administrative assistance, mediation, and persuasive approaches based on social-religious relations. These findings indicate that conflict management in mosque organizations requires not only technical governance but also institutional strengthening and participatory communication.